Initiating a used cooking oil collection network: An SCP–TSP approach within the circular economy framework - Siti Mahsanah Budijati; Fatma Hermining Astuti; Rafly Raihan Afendi (OPSI, 2026)
Used cooking oil (UCO) management is a critical challenge in advancing circular economy practices. While UCO poses environmental risks, it also offers economic potential, yet collection systems remain inefficient. This study introduces a spatially optimized network model focusing on distance efficiency and service coverage. The Set Covering Problem (SCP) was applied to determine optimal collection points, while the Traveling Salesman Problem (TSP) was used to design transportation routes to centralized facilities. Data from 101 food service businesses in Bantul, with 28 willing to serve as candidate sites, were analyzed. SCP results identified 12 optimal points covering all sources within a 5 km radius. TSP application with two alternative centers produced efficient routes: BUMDes Panggung Lestari (95.7 km; IDR 76,560) and DLH Bantul (95.4 km; IDR 76,320). These findings highlight the effectiveness of SCP–TSP integration in reducing costs and expanding coverage. The novelty lies in combining SCP and TSP within a single framework using district-level empirical data, bridging national circular economy policy with local implementation. This study provides practical guidance for sustainable UCO collection and supports circular economy strategies through resource recovery, while theoretically enriching discourse by demonstrating how SCP–TSP integration operationalizes resource recovery in quantitative terms.